Analysis of students understanding on biomimicry design approach - Wan Omar, Wan Noor Faaizah; Sharudin, Haszlin; Ahmad, Muhammad Azroll; Azizan, Hasnul Azwan; Mohd Yusof, Fadila; Ahmad, Anis Mardiana; Abd Rahman, Khairul Aidil Azlin (IJAS Publications, 2017)
Understanding is a common term used to describe comprehension. Comprehension is the act of grasping the meaning, nature or, importance of; in a more formal context. Understanding is classified as science in the field of psychological studies, where one has a firm acquirement of a specific topic, subject matter, situation and, or emotional consideration of which they seek, want and need to know. In an executive environment, a clear understanding is a crucial factor in the process of formation and strategic planning for the execution of a work flow. A thorough comprehension or understanding produces effective thinking process towards achieving the desired result. In the context of this research, the understanding process is being measured from the point of understanding the process of the biomimicry approach in the design process in particular. With the application of the Likert Measurement Method, this research will measure the level of individual understanding of the biomimicry approach in the design process. Biomimicry is a field that explores the human understanding of nature and its functions with the aim of producing a sustainable solution to human challenges by imitating nature’s tested patterns and strategies. In the context of this study, explanations and discussions will focus on the importance of comprehension in the implementation of biomimicry approach in design. The process of understanding will focus on finding the important attributes vis-à-visthe biomimicry approach.